Preferred methods of learning vocal repertoire among voice students from music education department Faculty of music, UiTM / Nur Ashyikin Mahmud - Mahmud, Nur Ashyikin (2014)
The purpose of this study was to investigate the preferred method of learning new vocal repertoire among voice students in the Department of Music Education in, UiTM. Voice students in UiTM take practical one-to-one voice classes called Major Instrument. Apart from that they also take Performing Groups (Choir) and other classes such as Music theory, Music history and music education classes as well, all of which demands a lot of time and effort to manage time for study and do assignments. Voice students learn 5 vocal repertoires every semester. This present research was conducted to investigate how voice students learn their vocal repertoire, how they practiced learning their vocal repertoire using their preferred methods, and the perceived advantages and disadvantages of their preferred method. The sample comprised of 12 students, 6 males and 6 females from Year 1 to 3 the overall finding showed that voice students go through many stages when learning their repertoire. The study looked at whether students preferred using the manual learning method or learning through the use of technology. The overall finding concluded that voice students have to go through a lot of process to learn their vocal repertoire. Out of 12 respondents 70% of the voice students who participated in the study often used the technology method-compared to 30% of voice students who used the manual learning.